Spark plasma sintering of WC-Ti powder mixtures and properties of obtained composites. Issue 5 (May 2022) - Garbiec, Dariusz; Laptev, Alexander M.; Leshchynsky, Volf; Wiśniewska, Maria; Figiel, Paweł; Biedunkiewicz, Anna; Siwak, Piotr; Räthel, Jan; Pötschke, Johannes; Herrmann, Mathias
Abstract: Three WC-Ti powder mixtures with 5, 10 and 15 wt% titanium were sintered by the spark plasma sintering technique. The microstructures and phase compositions of the samples were investigated by SEM, STEM, EBSD and XRD. The samples consisted of WC, W2 C and a (W1- x T x )C phases when the starting amounts of titanium were 5 and 10 wt%. At the titanium content of 15 wt% the microstructure of the samples included W2 C, (W1- x T x )C phases and elemental tungsten. The solubility of WC in TiC with the appearance of the (W1- x T x )C phase depended on the stoichiometry of the starting powder composition and sintering temperature. The results of EBSD phase mapping and the XRD investigation are in good agreement with the molar analysis. The best combination of hardness and fracture toughness was achieved with 5 wt% titanium. The appearance of elemental tungsten after sintering the WC-15Ti composition led to a significant reduction in hardness.